2023
DOI: 10.3390/en16020724
|View full text |Cite
|
Sign up to set email alerts
|

Design and Comprehensive Analyzes of a Highly Efficient TLA-Type Synchronous Reluctance Machine including the Effects of Conductor per Slot and Wire Size

Abstract: Consuming energy sources and greenhouse gas emission are one of the most prominent problems of the latest century. Most of the energy consumed globally and carbon dioxide emissions originate from electric motors used in the industry. Therefore, researchers have recently focused on the production of highly efficient, eco-friendly, and low-priced machines: Synchronous Reluctance Machines. In this study, the design and comprehensive Finite Element Analysis of a TLA-SynRM including the effects of the number of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Electric vehicles based on purely synchronous reluctance traction motors have yet to be commercially available [117]. Although it has been known for years that SynRMs can reach IE4 level efficiency [118,119], it has also been newly revealed that it can reach ultrapremium efficiency (IE5) [120]. However, the power factor of this type of electric motor is low [117,121], which necessitates a higher current-rated inverter.…”
Section: Comparison Of Different Machine Types With Rare-earth Elemen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Electric vehicles based on purely synchronous reluctance traction motors have yet to be commercially available [117]. Although it has been known for years that SynRMs can reach IE4 level efficiency [118,119], it has also been newly revealed that it can reach ultrapremium efficiency (IE5) [120]. However, the power factor of this type of electric motor is low [117,121], which necessitates a higher current-rated inverter.…”
Section: Comparison Of Different Machine Types With Rare-earth Elemen...mentioning
confidence: 99%
“…Although it has been known for years that SynRMs can reach IE4 level efficiency [118,119], it has also been newly revealed that it can reach ultra-premium efficiency (IE5) [120]. One cause for the unavailability is the low power factor [117,121], which necessitates a higher current-rated inverter.…”
Section: Electric Machine Design With Circular Economy Aspects In Ele...mentioning
confidence: 99%